MOTIVASI MOBILITIAS SOSIAL TOKOH JAY GATSBY DI ERA JAZZ AGE DALAM NOVEL THE GREAT GATSBY KARYA F. SCOTT FITZGERALD - Dwi Ario Fajar (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
This  study  entitled  "Motivation  of  Social  Mobility  in  the  novel  The  Great  Gatsby  by.  F.  Scott Fitzgerald".  The  author  is  interested  in  researching  the  novel  because  there  is  social  mobilit  y  reflected  through  the  character,  Jay  Gatsby.  The  purpose  of  this  study  is  to  reveal  forms  of  social mobility and motivation of character; To achieve the goals, the authors used a combined approach of structural  and  sociological  approach  to  literature.  The  structural  approach  used  to  assess  the intrinsic aspects of the novel, character and background, while the sociological approach to literature using  the  theory  of  social  mobility  to  assess  the  social  mobility  of  the  character‟  motivation  to improve and maintain his social class. In this novel, there is found kind of social mobility that done Jay  Gatsby. It is vertical social  mobility.  Vertical social  mobility  is  divided into  two  forms,  upward and downward. Vertical social mobility, up from the characters increase the level of the economy and increase social class through work and marriage. There are some motivation behind social mobility such as increasing and maintaining social class. Social mobility that occurs in the novel The Great Gatsby become an author's ideas reflect author‟s the social conditions. Through his ideas, the author intends to criticize how the importance of social class and social conditions of 1920s America while experiencing economic growth that brings influence to the people in hedonism and consumerism. So they do their social mobility in order to increase their economy level by the end justify the means.Keywords: novel, structural approach, sociology of literature, social mobility